Cytosine methylation and hydroxymethylation at the leptin promoter - Al-Azzawi, Haneen (2013)
Leptin is an important hormone well known for its role in regulating energy intake and expenditure. DNA methylation levels at the leptin promoter in adult tissues appear to correlate with environmental stresses experienced during early life. This suggests that, once established in early life, DNA methylation is stably transmitted over successive cell generations. The aim of the work presented in this thesis was to determine factors that contribute to the establishment and maintenance of this epigenetic mark at the leptin promoter and to investigate the individual roles of cytosine methylation and cytosine hydroxymethylation at this genomic locus. No effect of a high fat prenatal diet was observed on leptin promoter DNA methylation levels in the adipose tissue of pigs. However, this genomic region exhibited intermediate levels of DNA methylation, which is usually associated with gene silencing, even though adipose tissue is the primary site of leptin expression. Double stranded methylation data obtained from DNA methyltransferase (DNMT) mutant mouse embryonic stem cells (mESCs) was used to investigate the contributions of the three catalytically active DNMT enzymes to leptin promoter DNA methylation patterns. Depletion of DNMT3b resulted in increased methylation levels at the leptin promoter, consistent with preliminary data from mutant DNMT3b mouse tissues where similar increases in methylation levels were observed at specific CpG dinucleotides. Two mESC lines, either hypomethylated or hypermethylated at the leptin promoter, were tested for leptin mRNA expression and neither cell line expressed leptin mRNA, suggesting that some form of methylation may be required for leptin expression. To further investigate the relationship between DNA methylation and leptin expression, in vitro differentiated adipocytes were analysed. 3T3-L1 preadipocytes, which do not express leptin, exhibit high levels of DNA methylation and these high methylation levels are maintained after the cells differentiate into leptin-expressing adipocytes. Induction of cytosine hydroxymethylation at the leptin promoter was detected in differentiating and mature adipocytes and evidence is presented to suggest that cytosine hydroxymethylation at the leptin promoter correlates with leptin expression.